PEDAGOGICAL DISCOURSE AND ITS THEORETICAL FRAMEWORKS - Rakhmatullayeva , Khadicha Muhammad Zarif qizi (Innovative Development in Educational Activities, 2023)
The article explains how the method of analysis works by discussing Bernstein’s work on pedagogic discourse, using Halliday’s functional grammar to analyze a short excerpt from an early childhood curriculum genre, and demonstrating how the pedagogic discourse operates in an upper primary social science classroom. Overall, the article aims to contribute to our understanding of how individuals acquire shared knowledge and independent understanding within a culture through pedagogic discourse.